Automated 96-well format high throughput colony formation assay for siRNA library screen - Hatch, Stephanie B.; Prevo, Remko; Chan, Tiffany; Millar, Val; Cornelissen, Bart; Higgins, Geoff; Ebner, Daniel (STAR protocols, 2022)
The colony formation assay is the gold-standard technique to assess cell viability after treatment with cytotoxic reagents, ionizing radiation, and cytotoxic combinatorial treatments. This protocol describes a high-throughput automated and high-content imaging approach to screen siRNA molecular libraries in HeLa cervical cancer cells in 96-well format. We detail reverse transfection of cells with siRNAs, followed by ionizing radiation, fixing, and staining of the plates for automated colony counting. This protocol can be used across a broad range of cell types. For complete details on the use and execution of this protocol, please refer to Tiwana et al. (2015). [Display omitted] •High throughput screening (HTS) colony formation assay using liquid handling robots•Screens siRNA molecular libraries in HeLa cervical cancer cells in 96-well format•Automated colony counting and high content imaging readout approaches•Statistical analysis for HTS quality control and quantification Publisher's note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics. The colony formation assay is the gold-standard technique to assess cell viability after treatment with cytotoxic reagents, ionizing radiation, and cytotoxic combinatorial treatments. This protocol describes a high-throughput automated and high-content imaging approach to screen siRNA molecular libraries in HeLa cervical cancer cells in 96-well format. We detail reverse transfection of cells with siRNAs, followed by ionizing radiation, fixing, and staining of the plates for automated colony counting. This protocol can be used across a broad range of cell types.